IMPLEMENTATION OF THE CHARACTER OF RESPONSIBILITY IN LECTURE ACTIVITIES - Ratumbuysang, Monry Fraick Nicky Gillian; Nazaria, Raihan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
Responsibility can be interpreted as a person's attitude or behavior where he must carry out his obligations and duties as he has done towards himself, his family, society and also the surrounding environment. This research uses the Systematic Literature Review method. The number of articles found was 12 articles which were then grouped based on the same concept and discussion as the topic raised. The results of this study are (1) the implementation of the character of responsibility in lecture activities can be done by completing assignments, guidance, spontaneous activities, getting used to giving motivation, class rules, discussion activities, delivering lesson material and reflection activities which are carried out thoroughly in learning activities. In practice, students are required to carry out their responsibilities to be involved in lecture activities and carry out learning assignments. (2) students' responsible character can be built through character education using the habituation method, creating a conducive atmosphere and integrating its implementation in lectures. Habituation, creating a conducive and integrated atmosphere in lectures can be done using the Problem Based Learning (PBL) learning model (3) Apart from using the Problem Based Learning learning model, the formation of responsible character using the habituation method can also be built through the Contextual Teaching and Learning learning model or commonly called CTL. Applying this model, each member in the group will have their own role to increase their sense of responsibility and ability to solve problems. The contextual approach focuses on active student involvement in combining some material with the surrounding environment.